FAKTOR YANG MENENTUKAN KEPERCAYAAN MUZAKKI MEMBAYAR ZIS DI LEMBAGA PENGELOLA ZAKAT PASCA PEMBERITAAN KASUS ACT DI MEDIA MASSA (STUDI KASUS MUZAKKI DI WILAYAH JABODETABEK) - Paujiah, Rida; Munawar, Wildan; Kurnia, Tuti (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
The aim of this research is to determine the factors that determine muzakki's confidence in paying ZISat Zakat management institutions after the reporting of the Aksi Cepat Tunjung (ACT) case in the massmedia. The type of research carried out uses quantitative research with survey research methods. Thesample was taken using a purposive sampling technique, involving 100 respondents as the total samplefrom Jabodetabek Muslims who were aware of the ACT Case News and had paid their ZIS to the zakatmanagement institution. The analytical method used is factor analysis with the help of IBM SPSS version25. The findings from this research indicate that the factors that determine muzakki's confidence inpaying ZIS at the Zakat management institution after the reporting of the ACT Case in the Mass Mediaare, Factors that shape muzakki behavior consisting of muzakki culture, Muzakki Mass Media, MuzakkiReligiosity, Muzakki Social Environment and Muzakki Self-Awareness. Furthermore, Muzakki's trustfactor consists of Zakat Institution Transparency, Zakat Institution Image and ZIS Knowledge. Thedominant factors come from the factors that shape muzakki behavior